The mad, mad, mad world of climatism mankind and climate change mania - Goreham, Steve (New Lenox Books, 2012)
Using figures, cartoons, and whimsical sidebars, Steve Goreham describes our crazy world, which is far down the primrose path of global warming fantasy. Contrary to popular consensus, global warming is natural and cars are innocent. But this book is not short on science. Goreham uses charts, graphs, and references to dozens of scientific papers to support his arguments. He shows that icecap melting, stronger storms, polar bear extinction, and many other climate fears are unfounded